Răspuns :
(5-2X)(5+2X)+(1-4X)²
(5-2X)(5+2X) se aplica: (a-b)(a+b)=(a²-b²) deci
(5-2X)(5+2X)=25-4x²
iar pentru (1-4X)² se aplica (a-b)²=a²-2ab+b² deci
(1-4X)² =1-8x+16x²
inlocuind in expresia initiala va rezulta:
=25-4x²+1-8x+16x²
=12x²-8x+26
(5-2X)(5+2X) se aplica: (a-b)(a+b)=(a²-b²) deci
(5-2X)(5+2X)=25-4x²
iar pentru (1-4X)² se aplica (a-b)²=a²-2ab+b² deci
(1-4X)² =1-8x+16x²
inlocuind in expresia initiala va rezulta:
=25-4x²+1-8x+16x²
=12x²-8x+26
[tex](5-2x)(5+2x)+(1-4x)^2= 25-4x^2+1^2-2 \cdot 1 \cdot 4x+(4x)^2= \\ =25-4x^2+1-8x+16x^2=12x^2-8x+26[/tex]